2022
DOI: 10.1021/acsnano.2c04543
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PEG Antibodies Boosted in Humans by SARS-CoV-2 Lipid Nanoparticle mRNA Vaccine

Abstract: Humans commonly have low level antibodies to poly­(ethylene) glycol (PEG) due to environmental exposure. Lipid nanoparticle (LNP) mRNA vaccines for SARS-CoV-2 contain small amounts of PEG, but it is not known whether PEG antibodies are enhanced by vaccination and what their impact is on particle–immune cell interactions in human blood. We studied plasma from 130 adults receiving either the BNT162b2 (Pfizer-BioNTech) or mRNA-1273 (Moderna) mRNA vaccines or no SARS-CoV-2 vaccine for PEG-specific antibodies. Anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 42 publications
10
138
6
Order By: Relevance
“…1 shows the anti-PEG IgG (A) and IgM (B) levels and distribution in the blood of Covid-19 unvaccinated participants, and Table 1 lists the main statistical parameters derived from these data. Contrary to the 10-76% range of anti-PEG Ab positivity in various studies, 21,25,26,[30][31][32][33][34] we found detectable levels of these Abs in 98-99% blood donors. Their distribution was highly left-skewed, with considerable, 2-3 orders of magnitude span between the lowest and highest values.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…1 shows the anti-PEG IgG (A) and IgM (B) levels and distribution in the blood of Covid-19 unvaccinated participants, and Table 1 lists the main statistical parameters derived from these data. Contrary to the 10-76% range of anti-PEG Ab positivity in various studies, 21,25,26,[30][31][32][33][34] we found detectable levels of these Abs in 98-99% blood donors. Their distribution was highly left-skewed, with considerable, 2-3 orders of magnitude span between the lowest and highest values.…”
Section: Resultscontrasting
confidence: 99%
“…The discrepancy may partly be due to the diverse quantitation methods for anti-PEG Abs in these studies, 36 and partly to the different inclusion criteria of blood donors. For example, each referred reports on the prevalence of anti-PEG Abs in the healthy population or drug-treated patients 21,25,26,[30][31][32][33][34] used different antigens and/or differing test conditions in the anti-PEG Ab ELISA assays. As for the inclusion criteria of blood donors, we had a mixed population "enriched" with sporadic and chronic allergic people and patients with mastocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism underlying PEG immunogenicity is not completely understood, but two recent reviews have discussed the application of general knowledge regarding T-independent antigens to PEG immunogenicity through the passive immunization resulting from environmental exposure and food ( 153 , 154 ). Interestingly, two recent reports demonstrated anti-PEG IgG and IgM induction via active immunization with mRNA-PEG-LNPs in a pig model ( 155 ) and humans ( 156 ).…”
Section: Immunogenicitymentioning
confidence: 99%
“…Nanoparticle (NP)-based drug delivery systems that are capable of reducing nonspecific biodistribution in organs and tissues while specifically targeting tumors are needed to reduce systemic toxicity and improve drug delivery efficacy. Surface modification with poly­(ethylene glycol) (PEG), known as PEGylation, is a widely used approach to increase the colloidal stability of NPs and to reduce their interactions with a variety of components (e.g., proteins and immune cells) in biological environments. PEGylation can avoid NP clearance by the mononuclear phagocytic system and therefore improve the blood circulation time and the accumulation of NPs at tumor sites. , However, the injection of PEGylated NPs can stimulate the production of anti-PEG antibodies, which in turn results in complement activation and recognition by the immune system. , Consequently, repeated injection of PEGylated NPs induces the accelerated blood clearance (ABC) phenomenon, which reduces the blood circulation time of PEGylated NPs and their therapeutic efficacy. Recent work has shown that the mRNA NP vaccines used to combat the severe acute respiratory syndrome coronavirus 2 contain PEG-lipids that can also boost the levels of anti-PEG antibodies . This increase in anti-PEG antibody levels is associated with the increased association of PEGylated NPs to human blood immune cells and high reactogenicity.…”
Section: Introductionmentioning
confidence: 99%